Knowledge Classification on Ethnic Groups in Thailand. Issue 2 (17th February 2017) - Chaikhambung, Juthatip; Tuamsuk, Kulthida
ABSTRACT: This research aimed to analyze and develop a scope of knowledge and structure with respect to ethnic groups in Thailand. The research was conducted on the basis of the knowledge organization concept and principles of classification. This was a quality research that used content analysis method. It consisted of three processes: (1) identification of the scope of knowledge; (2) the development of knowledge classification and structure; and (3) evaluation and confirmation of the knowledge structure by experts. The research results provided the knowledge scope and structure of the ethnic groups in Thailand which comprises of 12 classes, 51 sub-classes, and 65 divisions. This knowledge structure can be used for ontology development or used as guidelines for subject headings and search terms in the information system.